ANALISIS IMPLIKATUR PADA KOLOM MANG USIL DALAM SURAT KABAR HARIAN KOMPAS DAN IMPLIKASINYA DALAM PEMBELAJARAN BAHASA INDONESIA DI SMA - Syahru Ramadan; Helena Emma Maria M.; Usman Usman (Universitas Negeri Makassar, 2016)
Abstract. Analysis of Implicature in Column Mang Usil in Kompas Daily Newspapers and Their Implications in Learning Indonesian in High School. The purpose of this research was to (1) describe the form of implicatures in Column Mang Usil at Kompas Newspaper, (2) describe the function of implicature in Column Mang Usil at Kompas Newspaper. This research is a qualitative descriptive study analyzing Mang Usil corner column in Kompas Daily Newspapers. Instruments used in this research is researcher and matrix form and function implicatures. Data in this research is written utterances contained in Mang Usil column in the Kompas Daily Newspaper June 2015, while the data source of this research is the Kompas Daily Newspaper. Data collection technique used in this research is the technique of reading, and record. The result showed that (1) the form of implicatures obtained in Column Mang Usil at Kompas Daily Newspapers consists of three types: declarative sentences consisting of declarative active and passive, imperative sentences consisting of imperative ordinary and prohibitions, and interrogative, (2) Function implicatures obtained in Column Mang Usil at Kompas Daily Newspapers consists of seven types, which function in the form of statements, functions in the form of satire, functions in the form of criticism, functions in the form of appreciation, functions such as support, functions in the form of a ban, and functions such as command, (3) the results of this study can be implicated in learning Indonesian Language in senior high school that is in the learning activities anecdotes text as one alternative learning resources in producing the text anecdotes on high school students grade X.